2012
DOI: 10.1161/hypertensionaha.111.189142
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvasculature as a Model to Study the Manifestations of Hypertension

Abstract: The retinal vasculature allows direct noninvasive visualization of the body’s mircrovasculature. Because the retina and other end organs (brain and kidney) share similar anatomical features and physiological properties, the retinal vessels offer a unique and easily accessible window to study the health and disease of the human microcirculation. Advanced retinal vascular imaging technologies have been developed to allow a more objective and precise assessment of retinal vascular changes. The changes in the reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
174
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(178 citation statements)
references
References 124 publications
1
174
0
3
Order By: Relevance
“…Vascular injury and remodeling is the common pathological sequelae in hypertension. 31 GAS5 knockdown affected arterial remodeling in hypertension in SHR. Moreover, blood pressure had the same changing trend as that of vascular remodeling on GAS5 knockdown.…”
Section: Discussionmentioning
confidence: 95%
“…Vascular injury and remodeling is the common pathological sequelae in hypertension. 31 GAS5 knockdown affected arterial remodeling in hypertension in SHR. Moreover, blood pressure had the same changing trend as that of vascular remodeling on GAS5 knockdown.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to the well-known association between narrow arteriolar calibers and coexisting hypertension (30)(31)(32), a meta-analysis and data pooling study showed that narrow retinal arteriolar calibers appear to precede clinical hypertension (33). Therefore, a plausible explanation for the link between narrower arteriolar caliber and incident DN seen in this population, compared with previously studied cohorts, is a higher prevalence of hypertension after the baseline examination.…”
Section: Discussionmentioning
confidence: 99%
“…Several longitudinal studies among adults have shown that retinal arteriolar narrowing, likely indicative of increased peripheral vascular resistance, is associated with increased risks of hypertension in later life, and can therefore be used as an early marker of cardiovascular disease risk. 11,27 Also, studies among children aged 6 to 8 and 12.7 years have shown that narrower retinal arterioles were significantly correlated with increased risks of hypertension. 12 Our results suggest that reduced maternal second trimester PlGF levels, which are associated with a suboptimal placenta development and the risk of adverse pregnancy outcomes, 7,8 might also lead to narrowing of microvasculature in later life.…”
Section: Interpretation Of Main Findingsmentioning
confidence: 99%